Aftershocks: Disruptive growth in low earth orbit creates new policy challenges - Ruth Stilwell (Centre for International Governance Innovation (CIGI), 2025)
The emergence of large constellations of small satellites has disrupted the field of space safety services and changed how we think about the risk of collisions in space. The risk from space debris is compounded by the growing congestion from operational satellites in low-Earth orbit, particularly between 300 and 700 km above the Earth. These satellites have created an opportunity for commercial operators to assume roles that were once the exclusive domain of military or other state actors. While increasing commercial interest in providing the essential safety functions of space situational awareness and conjunction alerting may increase the pace of innovation, and emerging technologies may enable new approaches to reduce collision risk on orbit, there are associated core governance issues of safety, sustainability and security in outer space that must be considered.
Keywords: 330